Visiting Albert and Rose Watkins And Friends in Southern California - Watkins, Howard::::::::: (1983)
Christine Watkins holding Robin Watkins, Lois Gardner, Albert Watkins, Lou Gardner, Rose Watkins and Adam Watkins, Batsheva Eitan, and family friend